2023
DOI: 10.1101/2023.01.08.523127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bivalent mRNA vaccine improves antibody-mediated neutralization of many SARS-CoV-2 Omicron lineage variants

Abstract: The early Omicron lineage variants evolved and gave rise to diverging lineages that fueled the COVID-19 pandemic in 2022. Bivalent mRNA vaccines, designed to broaden protection against circulating and future variants, were authorized by the U.S. Food and Drug Administration (FDA) in August 2022 and recommended by the U.S. Centers for Disease Control and Prevention (CDC) in September 2022. The impact of bivalent vaccination on eliciting neutralizing antibodies against homologous BA.4/BA.5 viruses as well as eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
2
2
0
1
Order By: Relevance
“…Consistent with our data, there is epidemiological evidence indicating that bivalent vaccines provide significant additional protection against symptomatic Omicron infection and hospitalization 3,4 . Of note, our results showed only modestly increased BA.5 neutralization, which is in agreement with previous studies [5][6][7][8][9][10][11][12] , whereas others suggested that the bivalent-BA.4/BA.5 vaccine would not be more effective than the original monovalent vaccine [13][14][15] . The bivalent-BA.1 booster induced similarly high neutralization titers as the bivalent-BA.4/BA.5 booster (Figure 1a), but significant differences were not observed relative to the monovalent vaccine, which is in line with previous studies 6 .…”
Section: Textsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our data, there is epidemiological evidence indicating that bivalent vaccines provide significant additional protection against symptomatic Omicron infection and hospitalization 3,4 . Of note, our results showed only modestly increased BA.5 neutralization, which is in agreement with previous studies [5][6][7][8][9][10][11][12] , whereas others suggested that the bivalent-BA.4/BA.5 vaccine would not be more effective than the original monovalent vaccine [13][14][15] . The bivalent-BA.1 booster induced similarly high neutralization titers as the bivalent-BA.4/BA.5 booster (Figure 1a), but significant differences were not observed relative to the monovalent vaccine, which is in line with previous studies 6 .…”
Section: Textsupporting
confidence: 93%
“…The bivalent-BA.1 booster induced similarly high neutralization titers as the bivalent-BA.4/BA.5 booster (Figure 1a), but significant differences were not observed relative to the monovalent vaccine, which is in line with previous studies 6 . XBB.1.5-NT titers were lowest in all groups (Figure 1a), which confirms the strong escape of this variant from current vaccine-and infection-elicited neutralizing antibodies 8,9,16 A comparison of NT titers between sera obtained on the day of booster and those one month later showed that the bivalent-BA.1 vaccine yielded the strongest increase in BA.1-NT titers (Figure 1b).…”
Section: Textsupporting
confidence: 58%
“…In particular, XBB.1.5 has immune escape ability against neutralizing antibodies produced by omicrontype bivalent vaccines [(conventional strain (strain of origin)/Omicron strain BA.1) or (conventional strain (strain of origin)/Omicron strain BA.4-5)]. There are currently no antibody drugs that exhibit effective neutralizing antibody activity against XBB.1.5 (99,121,(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144). This is because mutations in the Spike molecule change the conformation of the Spike, and the neutralizing activity of the antibody is easily lost.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, XBB.1.5 has immune escape ability against neutralizing antibodies produced by omicrontype bivalent vaccines [(conventional strain (strain of origin)/Omicron strain BA.1) or (conventional strain (strain of origin)/Omicron strain BA.4-5)]. There are currently no antibody drugs that exhibit effective neutralizing antibody activity against XBB.1.5 (99,121,(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144). This is because mutations in the Spike molecule change the conformation of the Spike, and the neutralizing activity of the antibody is easily lost.…”
Section: Discussionmentioning
confidence: 99%